ANALISIS HARGA POKOK PRODUKSI SEBAGAI DASAR PENETAPAN HARGA JUAL UMKM ABIG BERKAH - Niken Safitri; Rizky Maulana; Sandi Setiadi; Fithri Suciati (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2025)
This study aims to analyze the calculation of the Cost of Production (COP) as a basis for determining the selling price at UMKM Kedai Abig Berkah in Sukabumi. Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy; however, they often face structural challenges in implementing accurate production cost recording systems. The main problem identified is the use of a very simple and unsystematic COP calculation practice, in which the owner only sums up the main raw material costs and direct labor costs, without including factory overhead costs such as depreciation of kitchen equipment and utility expenses in detail. This research employs a qualitative descriptive approach, with data analysis methods consisting of data reduction, data presentation, and conclusion drawing. The findings reveal a significant discrepancy between the MSME’s internal calculation of Rp18,290 per portion and the application of the full costing method, which results in a COP of Rp36,360 per portion. Using a cost-plus pricing approach with a target profit margin of 15%, the recommended selling price is Rp42,000 per portion, which is Rp16,841 higher than the current selling price of Rp25,000. In conclusion, inaccurate COP calculation leads to underpricing, which potentially undermines profit margin stability and business competitiveness. Therefore, the implementation of comprehensive cost accounting is essential as a foundation for sustainable business strategy